2003
DOI: 10.1037/1528-3542.3.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Separating emotion and motivational direction in fear and anger: Effects on frontal asymmetry.

Abstract: State effects on frontal alpha electroencephalograph asymmetry (ASY) are thought to reflect approach and withdrawal motivational tendencies. Although this motivational direction model has inspired a large body of research, efforts to disentangle influences of emotion (EMO) and motivational direction (MOT) on ASY are rare. The authors independently manipulated EMO (fear and anger) and MOT (approach and withdrawal) in a between-subjects design. Irrespective of MOT, anger led to greater changes toward relative le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
115
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 40 publications
(75 reference statements)
21
115
3
Order By: Relevance
“…This suggestion was inspired by Harmon-Jones and Allen (1997), who reported on a relation of higher bilateral frontal cortical activity and higher scores on the BAS scale. Behavioral activation comprising approach and withdrawal motivation would also be in line with Wacker et al's (2003) arguments in favor of a relation of the BAS with behavioral activation irrespective of the direction of behavior. So, they had two hypothesis to test: the BIS/BAS model, and the bilateral BAS model.…”
Section: Asymmetrical Frontal Brain Activity and Angersupporting
confidence: 57%
“…This suggestion was inspired by Harmon-Jones and Allen (1997), who reported on a relation of higher bilateral frontal cortical activity and higher scores on the BAS scale. Behavioral activation comprising approach and withdrawal motivation would also be in line with Wacker et al's (2003) arguments in favor of a relation of the BAS with behavioral activation irrespective of the direction of behavior. So, they had two hypothesis to test: the BIS/BAS model, and the bilateral BAS model.…”
Section: Asymmetrical Frontal Brain Activity and Angersupporting
confidence: 57%
“…For example, Wacker et al (2003) demonstrated that relative activation patterns of the left anterior region in response to imagining a past event that elicited anger were strongly correlated with scores on measures of BAS. Building from the evidence produced by Harmon-Jones and Allen (1998) regarding the utility of resting anterior cortical activation to predict trait anger, researchers have shown that resting relative activation of the left anterior region is associated with measures of BAS and trait anger (Hewig et al 2004).…”
Section: Approach-withdrawal Modelmentioning
confidence: 97%
“…An extension of Davidson's model by Heller (Heller et al, 1997;Heller and Nitschke, 1998) adds the arousal dimension, associated with the right parietal cortex activity. Davidson's approach and withdrawal systems are somewhat similar to Gray's behavioral activation and inhibition systems (BAS and BIS, respectively) (Gray, 1994;Wacker et al, 2003). The BAS is hypothesized to control appetitive and goal-directed behavior and becomes activated in response to incentive, reward, and other positive stimuli.…”
mentioning
confidence: 98%